The small molecule activator S3969 stimulates the epithelial sodium channel by interacting with a specific binding pocket in the channel's β-subunit - Sure, Florian; Einsiedel, Jürgen; Gmeiner, Peter; Duchstein, Patrick; Zahn, Dirk; Korbmacher, Christoph; Ilyaskin, Alexandr (Journal of Biological Chemistry, 2024)
The epithelial sodium channel (ENaC) is essential for mediating sodium absorption in several epithelia. Its impaired function leads to severe disorders, including pseudohypoaldosteronism type 1 and respiratory distress. Therefore, pharmacological ENaC activators have potential therapeutic implications. Previously, a small molecule ENaC activator (S3969) was developed. So far, little is known about molecular mechanisms involved in S3969-mediated ENaC stimulation. Here, we identified an S3969-binding site in human ENaC by combining structure-based simulations with molecular biological methods and electrophysiological measurements of ENaC heterologously expressed in Xenopus laevis oocytes. We confirmed a previous observation that the extracellular loop of β-ENaC is essential for ENaC stimulation by S3969. Molecular dynamics simulations predicted critical residues in the thumb domain of β-ENaC (Arg388, Phe391, and Tyr406) that coordinate S3969 within a binding site localized at the β-γ-subunit interface. Importantly, mutating each of these residues reduced (R388H; R388A) or nearly abolished (F391G; Y406A) the S3969-mediated ENaC activation. Molecular dynamics simulations also suggested that S3969-mediated ENaC stimulation involved a movement of the α5 helix of the thumb domain of β-ENaC away from the palm domain of γ-ENaC. Consistent with this, the introduction of two cysteine residues (βR437C – γS298C) to form a disulfide bridge connecting these two domains prevented ENaC stimulation by S3969 unless the disulfide bond was reduced by DTT. Finally, we demonstrated that S3969 stimulated ENaC endogenously expressed in cultured human airway epithelial cells (H441). These new findings may lead to novel (patho-)physiological and therapeutic concepts for disorders associated with altered ENaC function.
CRIS-Team Scopus Importer:2024-03-29
Keywords: electrophysiology; epithelial sodium channel (ENaC); H441 cell line; molecular docking; molecular dynamics; oocyte; S3969; site-directed mutagenesis; small molecule activator; two electrode voltage clamp